Rubber Band Ligation versus Excisional Haemorrhoidectomy A Search for Better Option (TAJ: Journal of Teachers Association, 2009)
During The period of March-2003 to January-2006 a total of 100 patients with haemorrhoid admitted in Jhenaidah Sadar Hospital and in different private clinics of Jhenaidah and Faridpur town were taken in the study. This study compares the two most popular treatment options for haemorrhoids namely rubber band ligation (R.B.L) and excisional haemorrhoidectomy (E.H). Complete Remission of haemorrhoidal symptoms was better after haemorrhoidectomy than rubber band ligation. Fewer Patients required retreatment after haemorrhoidectomy but anal stenosis, postoperative haemorrhage and incontinence of flatus were more common with this operation. Haemorrhoidectomy produced better long term symptom control in patients with grade III Haemorrhoid but was associated with more postoperative complications than rubber band ligation. doi: 10.3329/taj.v20i2.3069 TAJ 2007; 20(2): 107-109